Phytoestrogens are the correctors of vasomotor and psychoemotional reactions after experimental ovariectomy - T. M. Plotnikova; N. V. Vasiliyeva; A. M. Anishchenko (Бюллетень сибирской медицины, 2011)
The effects of Maackia amurensis extract (200 mg/kg, p.o. during the 14 days) on the vasomotor and psychoemotional reactions in rats after ovariectomy were investigated. The Maackia amurensis extract did not change the blood level of sex hormones, showed anxiolytic activity with the models of anxious disorders, did not influence considerably on the motor activity in «open field» test. Maackia amurensis extract reduced the pathological vasomotor reactions, showing by the change in vessels reactions on vasoactive agents and «hot flushes».